Exploring The Correlation between Motivation, Anxiety, Stress, and Hockey Athletes’ Confidence Before Competition - Sa'adah, Nafiatus; Widiyawati, Wiwik (STIKes Patria Husada Blitar, 2025)
Confidence is a key aspect of an athlete's performance, affecting motivation, performance, and stress management while competing. This study aimed to analyze the correlation between motivation, anxiety, and stress with the confidence of East Java hockey athletes before competition. The design of the study was cross-sectional. The population was 2024 PON hockey athletes aged 18-25 years totaling 60 athletes, namely 30 male athletes and 30 female athletes using the total sampling method. A quantitative descriptive research method was conducted with the DASS-42 questionnaire to measure anxiety and stress levels, as well as a questionnaire adopted for motivation and confidence. Of the 60 respondents, 73.3% of the athletes showed excellent motivation, while anxiety and stress ranged from normal to severe. Analysis using Spearman rank showed a significant correlation between motivation (p=0.001), anxiety (p=0.006), and stress (p=0.005) and self-confidence. Emphasize the importance of athletes' mental readiness in facing competition and the need for support and education regarding the management of psychological factors. Advice is given for coaches to strengthen mental support programs to increase athletes' confidence.